2019
DOI: 10.1016/j.jaci.2019.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Sox17 promotes allergic airway inflammation

Abstract: Background: IL-33, levels of which are known to be increased in patients with eosinophilic asthma and which is suggested as a therapeutic target for it, activates endothelial cells in which Sry-related high-mobility-group box (Sox) 17, an endothelium-specific transcription factor, was upregulated. Objective: We investigated the relationship between Sox17 and IL-33 and the possible role of Sox17 in the pathogenesis of asthma using a mouse model of airway inflammation. Methods: We used ovalbumin (OVA) to induce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 51 publications
2
8
0
Order By: Relevance
“…SOX17 is known as a transcriptional regulator that orchestrates arterial specification, endothelial integrity and modulates tip cell differentiation during vessel sprouting [ 51 , 52 , 53 ]. In line with the co-expression of ICAM1 and SOX17 in the PVC cluster, it has recently been shown that the level of SOX17 was markedly elevated in ECs upon inflammation, which was essential to the induction of ICAM1 expression and monocyte adhesion [ 54 ]. Arterioles and post-arterial capillaries share a high level of molecular similarities.…”
Section: Discussionmentioning
confidence: 99%
“…SOX17 is known as a transcriptional regulator that orchestrates arterial specification, endothelial integrity and modulates tip cell differentiation during vessel sprouting [ 51 , 52 , 53 ]. In line with the co-expression of ICAM1 and SOX17 in the PVC cluster, it has recently been shown that the level of SOX17 was markedly elevated in ECs upon inflammation, which was essential to the induction of ICAM1 expression and monocyte adhesion [ 54 ]. Arterioles and post-arterial capillaries share a high level of molecular similarities.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to NF-κB-dependent transactivation by TRIM28, RIPK3-mediated sequestration of TRIM28 from the chromatin can release repression on SOX9 transcriptional activity. SOX9-mediated repression of its target genes through TRIM28 was recently reported [ 45 ] and other SOX family members were also shown to correlate with activation or repression of TRIM28 target genes [ 46 , 47 ]. From SOX9 ChIP-Seq data, we can speculate that reduced TRIM28 binding from chromatin during TSZ stimulation may turn on SOX9-mediated transactivation to express cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…The vascular factor plays an important role in the development of the allergic process in the lungs. Endothelial cells express P-selectin, E-selectin, Sox17, intercellular adhesion molecules-1 (ICAM-1) and blood cell adhesion molecules (VCAM-1) [11]. On the other hand, the components of the vascular wall (endothelium, smooth myocytes, fibroblasts) are targets for neuroendocrine [12] and immune factors [10] of the development of allergic process in the lungs.…”
Section: Discussionmentioning
confidence: 99%